Implementasi Pendidikan Karakter di Pondok Pesantren Salafiyah Syafi’iyah Sukorejo - Rif’ah Rif’ah (DAR EL-ILMI : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2017)
AbstractPondok Pesantren is part of agencies that have a role in character education. Fukus research are: 1) implementation of the values of character; 2) Method of character education. Objectives are: 1) describe the implementation of the values of character; 2) Describe the method of character education. Methods: Qualitative approach with phenomenological type. Mechanical Sampling purposive sampling and snowball sampling. Data collection techniques: interview, observation and documentation. Mechanical Analysis of field data: data reduction, data presentation and verification of data / conclusions. Results: 1) The values karkter developed form: the five compulsory congregational prayers, all students must enter madrasah diniyah in the morning, the Qur'an to be the standard rise and graduation, call the chaplain and ustadza to teachers, students Separation the sons and daughters, organizational activities to build creativity, Care for the environment with picket hygiene, national spirit with the commemoration of the great days. Method of Character Education: Understanding, Awareness and Practice. Benefits Research: a reference and study for school pupils, students, teachers, faculty and the community to the next can be carried out.